The estimation of patients' views on organizational aspects of a general dental practice by general dental practitioners: a survey study - Truin Gert-Jan; Bronkhorst Ewald M; Wensing Michel; Sonneveld Rutger E; Brands Wolter G (BMC, 2011)
Abstract Background Considering the changes in dental healthcare, such as the increasing assertiveness of patients, the introduction of new dental professionals, and regulated competition, it becomes more important that general dental practitioners (GDPs) take patients' views into account. The aim of the study was to compare patients' views on organizational aspects of general dental practices with those of GDPs and with GDPs' estimation of patients' views. Methods In a survey study, patients and GDPs provided their views on organizational aspects of a general dental practice. In a second, separate survey, GDPs were invited to estimate patients' views on 22 organizational aspects of a general dental practice. Results For 4 of the 22 aspects, patients and GDPs had the same views, and GDPs estimated patients' views reasonably well: 'Dutch-speaking GDP', 'guarantee on treatment', 'treatment by the same GDP', and 'reminder of routine oral examination'. For 2 aspects ('quality assessment' and 'accessibility for disabled patients') patients and GDPs had the same standards, although the GDPs underestimated the patients' standards. Patients had higher standards than GDPs for 7 aspects and lower standards than GDPs for 8 aspects. Conclusion On most aspects GDPs and patient have different views, except for social desirable aspects. Given the increasing assertiveness of patients, it is startling the GDP's estimated only half of the patients' views correctly. The findings of the study can assist GDPs in adapting their organizational services to better meet the preferences of their patients and to improve the communication towards patients.